Total endovenous recanalization and stent reconstruction for naïve non-inferior vena cava filter-associated chronic iliocaval occlusive disease: Placement of 352 venous stents in 69 debilitated patients. (August 2019) - McDevitt, Joseph L; Srinivasa, Ravi N; Hage, Anthony N; Bundy, Jacob J; Gemmete, Joseph J; Srinivasa, Rajiv N; Chick, Jeffrey Forris Beecham
The aim of this study was to report the technical success, adverse events, clinical outcomes, and long-term stent patency of iliocaval stent reconstruction for naïve, non-inferior vena cava (IVC) filter-related, chronic iliocaval thrombosis. A total of 69 patients, including 47 (68%) men, with a mean age of 36 years (range: 8–71 years), underwent first-time iliocaval stent reconstruction for non-IVC filter-associated iliocaval thrombosis. The mean number of prothrombotic risk factors was 2.2 (range: 0–5), including 30 (43%) patients with IVC atresia. Upon initial presentation, the Clinical, Etiology, Anatomy, and Pathophysiology (CEAP) classification was C3 in 55 (80%) patients, C4 in four (5.8%) patients, C5 in one (1.4%) patient, and C6 in seven (10%) patients. Technical aspects of stent reconstruction, technical success, adverse events, 2-week and 6, 12, and 24-month clinical response, and 6, 12, and 24-month primary, primary-assisted, and secondary stent patency rates were recorded. Technical success was defined as recanalization and stent deployment. Adverse events were reported according to the Society of Interventional Radiology classification system. Clinical success was defined as a 1-point decrease in CEAP classification and stent patency was defined by the Cardiovascular and Interventional Radiological Society guidelines. The technical success rate was 100%. There were 352 venous stents deployed during stent reconstructions. One (1.4%) severe, four (5.8%) moderate, and four (5.8%) minor adverse events occurred and median post-procedure hospitalization was 1 day (range: 1–45 days). Clinical success at 2 weeks and 6, 12, and 24 months was 76%, 85%, 87%, and 100%, respectively. The estimated 6, 12, and 24-month primary patency rates were 91%, 88%, and 62%, respectively. The estimated 6, 12, and 24-month primary-assisted patency rates were 98%, 95%, and 81%, respectively. The estimated 6, 12, and 24-month secondary-assisted patency rates were all 100%. In conclusion, iliocaval stent reconstruction is an effective treatment for non-IVC filter-associated chronic iliocaval thrombosis with high rates of technical success, clinical responses, and stent patency.